Dynamics of a Sporadic Nosocomial Acinetobacter calcoaceticus – Acinetobacter baumannii Complex Population - Villalón, Pilar; Ortega, Montserrat; Sáez-Nieto, Juan A.; Carrasco, Gema; Medina-Pascual, María J.; Garrido, Noelia; Valdezate, Sylvia (Frontiers in Microbiology, 2019)
Abstract Our objective was to improve current knowledge of sporadic nosocomial Acinetobacter calcoaceticus-Acinetobacter baumannii (Acb) complex populations, and thus better understand the epidemiology of sporadic and endemoepidemic strains. Between 1999 and 2010, 133 isolates of sporadic Acb complex were obtained from a single hospital. Species were identified by gyrB-PCR, and via gyrB- and rpoB-sequencing. Clonal analysis was undertaken using pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing. Susceptibility to antimicrobial agents was determined by microdilution and E-tests. Carbapenemase genes were detected by PCR. One hundred and one PFGE types were detected. A. baumannii was the most common (67/101 PFGE types), followed by A. pittii (22/101), A. lactucae (6/101), and A. calcoaceticus (2/101). gyrB, rpoB1, and rpoB2 sequencing returned 49, 13, and 16 novel sequences respectively. Sixty-three sequence types (STs) (38 new STs and 66 new alleles) were detected; the most common were ST2 (29/133 isolates) and ST132 (14/133). Twenty-six OXA-51 allelic variants were detected, nine of which were novel. The PFGE types were generally susceptible (88/101) to all the tested antimicrobials; 3/101 were carbapenem-resistant due to the presence of the genetic structure ISAba2-blaOXA-58-like-ISAba3, and 2/101 were multidrug-resistant. It can be concluded that the examined sporadic Acb complex population was mainly composed of A. baumannii. Many different clones were detected (with ST2 clearly dominant), all largely susceptible to antimicrobials; multidrug resistance was rare. In contrast, a previously examined endemoepidemic Acb population was composed of just four expanding, multidrug-resistant A. baumannii clones -ST2, ST3, ST15 and ST80-.